Stars and black holes: a transdisciplinary proposal - Correia, Lincoln; Ferreira, Roberto Claudino; Rocha Lima, Érika; Souza Leite, Freddy; da Silva Cruz, Maria Eduarda; Macêdo Ribeiro, Simone; Santos de Jesus, Vanessa (Cadernos de Astronomia, 2023)
This work comes from a scientific initiation research in education in astronomy and transdisciplinarity. The proposed objective was, through transdisciplinarity, to expose the theme “Stars and Black Holes”. The elaboration of the research began with bibliographic studies for the composition of a didactic text on the subject and culminated in an online seminar in the extension course modality. The research subjects were undergraduate students from the SUSB and other institutions, among them and other guests, 50 people attended. The lecture was conducted with alternating slides and the astronomical software Spaceengine, the conduction was guided by the transdisciplinary approach. We explore star systems showing from their "birth" to their "end" and black holes. We applied a questionnaire at the end of the presentation to collect the research results, for which we highlighted that 79.2% said that the transdisciplinary proposal was fruitful. Concluding then that the proposal fulfilled its transdisciplinary profile with good approval from the guests, but that it needs improvement in some aspects.
Keywords: Astronomy; Education; Transdisciplinarity